2005
DOI: 10.1086/427111
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Clarithromycin Prior to Coronary Artery Bypass Graft Surgery Does Not Prevent Subsequent Cardiac Events

Abstract: Treatment with clarithromycin in patients scheduled for CABG surgery did not reduce the subsequent occurrence of cardiovascular events or mortality during a 2-year follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 30 publications
1
20
0
3
Order By: Relevance
“…Six trials were conducted among patients with stable coronary artery disease (10,(13)(14)(15)(16)(17) and six trials involved patients with acute coronary syndromes (18)(19)(20)(21)(22)(23). The remaining trial was conducted among patients scheduled to undergo coronary artery bypass graft surgery (24). Three trials (10,13,14) included anti-Chlamydia immunoglobulin (Ig)G titres as part of their inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six trials were conducted among patients with stable coronary artery disease (10,(13)(14)(15)(16)(17) and six trials involved patients with acute coronary syndromes (18)(19)(20)(21)(22)(23). The remaining trial was conducted among patients scheduled to undergo coronary artery bypass graft surgery (24). Three trials (10,13,14) included anti-Chlamydia immunoglobulin (Ig)G titres as part of their inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Three trials (10,13,14) included anti-Chlamydia immunoglobulin (Ig)G titres as part of their inclusion criteria. Trials examined the use of one of four different antibiotics: azithromycin (seven trials) (10,(13)(14)(15)(19)(20)(21), roxithromycin (two trials) (17,22), clarithromycin (three trials) (16,23,24) and gatifloxacin (one trial) (18).…”
Section: Resultsmentioning
confidence: 99%
“…3 However, another randomised controlled trial, with follow-up of two years, showed that among patients receiving a coronary artery bypass graft, the rate of cardiovascular events was not significantly reduced with short term clarithromycin treatment compared with placebo. 5 On the contrary, a significantly higher risk of cardiovascular mortality was reported over three years and also a higher all cause mortality among patients with coronary heart diseases receiving a two week course of clarithromycin once daily compared with placebo over six years. 4 6 7 In addition to the randomised trials, a cohort study reported a substantially higher risk of cardiac death associated with use of clarithromycin compared with penicillin V over seven day's follow-up among the general population.…”
Section: Introductionmentioning
confidence: 96%
“…2 Several randomised controlled trials were conducted to explore the effects of clarithromycin on the prevention of cardiovascular outcomes among patients with cardiovascular disease. [3][4][5] Among these, the first randomised controlled trial showed that clarithromycin use for three months seemed to reduce the risk of cardiovascular outcomes in 1.5 years. 3 However, another randomised controlled trial, with follow-up of two years, showed that among patients receiving a coronary artery bypass graft, the rate of cardiovascular events was not significantly reduced with short term clarithromycin treatment compared with placebo.…”
Section: Introductionmentioning
confidence: 99%
“…18 Two year mortality was insignificantly raised in the clarithromycin patients (1.10, 0.44 to 2.76). 18 Pooling these data with our results shows a significantly increased mortality in clarithromycin patients (1.28, 1.05 to 1.57).…”
Section: Comparison With Related Researchmentioning
confidence: 88%